Nanomaterials as potential transporters of HDAC inhibitors - Cristabelle De Souza; Zhao Ma; Aaron Raymond Lindstrom; Biswa Prasun Chatterji (Elsevier, 2020)
Nanomedicine that combines technology with medical diagnostics and therapeutics is now advancing to greater heights for its significant potential in drug delivery. Epigenetic modifications that alter gene expressions patterns are often associated with disease progression and therapeutic resistance. Histone Deacetylase (HDAC) enzymes that are upregulated in Cancer and Alzheimer's are being highly researched as promising targets for treatment strategies. Even though there have been a spate of HDAC inhibitor drugs currently in clinical trials or in the market, side effects associated with toxicity and non specific targeting warrant the need for a better design for efficient drug delivery. To date there are very few clinically approved nanovectors and even fewer nanoparticles that can safely deliver HDAC inhibitors in vitro and in vivo. This review will examine the different types of nanomaterials that are currently available and enumerate the current studies being carried out with regard to nanomediated HDAC inhibitor delivery. We will discuss the challenges that face combining HDAC inhibitors with different nanoparticles and underscore the potential that exists to develop these strategies further with a specific focus on anti-cancer therapy.